DETECTION OF BACTERIAL SPECIES ASSOCIATED WITH PERIODONTAL DISEASE IN A GROUP OF PATIENTS - Cristina Vodiță; Doina Lucia Ghergic; Emanuel Alin Vodiță; Raluca Monica Comăneanu; Laurența Lelia Mihai (Amaltea Medical Publishing House, 2021)
Objectives. The study aimed to detect the presence/quantification of the 12 bacterial strains more frequently involved in the occurrence and aggravation of periodontal disease in a group of patients. Material and method. The study included 55 patients of both sexes, from the portfolio of the "Dr. Vodiță" Dental Clinic, with chronic marginal periodontitis, who had not been under regular dental control and hygiene for at least 2 years. During the first treatment session, fluid was collected from each patient from the periodontal bags using sterile paper cones from the collection putty. Subsequently, fluid-soaked paper cones from periodontal bags were sent to the Genetic Lab in Bucharest for DNA extraction and quantification of 12 bacterial species, more common in the etiology of periodontal disease. For the correctness of the results obtained, it is necessary that patients have not taken antibiotics in the last 3 weeks. The data were analyzed and statistically processed with the Microsoft Excel 2016 program. Results. The least common bacteria found were from the species: Capnocytophaga ochracea, Aggregatibacter actinomycetemcomitans, Eikanella corrodens and Campylobacter rectus, closely followed by Capnocytophaga gingivalis, Prevotella intermedia and Capnocytophaga sputigena. The rest of the bacterial species were detected much more frequently. Discussions. In the analyzed group there was no monoinfection with Aggregatibacter actinomycetemcomitans. Porphyromonas gingivalis had an important presence in the studied group, registering increased levels in 89% of cases. In our group, Treponema denticola was present in increased amounts in 76.36% of cases. Tannerella forsythia was present in 92.72% of cases in elevated concentrations. Eikanella corrodens and Campylobacter rectus were present in 18.18% of the cases studied in high quantities. Prevotella intermedia was present in significant amounts in 34.54% of cases. Fusobacterium nucleatum was present in high concentrations in 98.18% of the cases studied. Prevotella nigrescens was present in increased amounts in 56.36% of cases. Capnocytophaga ochracea was present in 9.09% of cases in high amounts, Capnocytophaga sputigena in 38.18% of cases, and Capnocytophaga gingivalis was detected in 24.45% of cases. Conclusions. From the class of bacteria with high pathogenicity, we most frequently encountered in the studied group Tannerella forsythia. From the class of bacteria with moderate pathogenicity, we encountered the most common Fusobacterium nucleatum. From the class of bacteria with low pathogenicity, we encountered the most common Capnocytophaga sputigena. In order to validate the results obtained, it is necessary to extend the study to a larger number of patients.